The sister effect eaudiobook - Mallery, Susan (Harlequin Audio, 2023)
,"Mallery beautifully illustrates the power of female friendship and the importance of reaching for one's dreams."—Publishers Weekly Beloved bestselling author Susan Mallery brings readers an emotional, witty, and heartfelt story that explores the nuances of a broken family's complex emotions as they strive to become whole in this uplifting story of human frailty and resilience. Finley McGowan is determined that the niece she's raising will always feel loved and wanted. Unlike how she felt after her mom left to pursue a dream of stardom, and when the grandfather who was left to raise them abandoned her and her sister, Sloane, when they needed him most. Finley reacted to her chaotic childhood by walking the straight and narrow—nose down, work hard, follow the rules. Sloane went the other way. Now Sloane is back, as beautiful and as damaged as ever...and she wants a relationship with her daughter. She says she's changed, but Finley's heart has been burned once too often for her to trust easily. But is her reluctance to forgive really about Sloane or worry over losing what she loves the most? With the help of a man who knows all too well how messy families can be, Finley will learn there's joy in surrendering and peace in letting go. Don't miss #1 New York Times bestselling author Susan Mallery's latest masterpiece, For the Love of Summer , a captivating story that weaves together the complexities of family, friendship, and unexpected bonds. Discover more from Susan Mallery: For the Love of Summer - Coming June 2024! The Summer Book Club The Sister Effect The Boardwalk Bookshop The Summer Getaway